The Association Between Fear of Coronavirus Disease 2019, Mental Health, and Turnover Intention Among Quarantine Hotel Employees in China - Teng, Yi-Man; Wu, Kun-Shan; Xu, Dan (Frontiers in Public Health, 2021)
During the Covid-19 pandemic, quarantine hotel employees face a higher risk of infection while they host quarantine guests from overseas. This is the first research to empirically test the psychological effect on the employees while operating a quarantine hotel. These figures indicate that heightened fear of COVID-19 leads to adverse mental health of quarantine hotel staff. The empirical results confirm that depression, anxiety, and stress have a significant influence on turnover intention. These ﬁndings contribute to the extant knowledge base by uncovering the role of mental health in employee turnover intention. Based on the results, implications are presented for practitioners.